Cross-Dressing and Transgender Representation in Swedish Cinema, 1908–2017 - Horak, Laura (European Journal of Scandinavian Studies, 2017)
Today’s explosion of Swedish films made by and about transgender people is sometimes considered in a vacuum. This article explores the long history of cross-gender performance in Swedish cinema and the relationship of these new films to older traditions. In this article, I will outline the contours of cross-gender performance in Swedish films from the 1908 to today, using some exemplary films to display the variety of styles, genres, and meanings that can be found: the short dance film Dances Through the Ages ( Skilda tiders danser , Walfrid Bergström, 1909); the swashbuckler Lasse-Maja (Gunnar Olsson, 1941); the romantic comedy Up With Little Märta ( Fram för Lilla Märta , Hasse Ekman, 1945); the dramatic art film The Magician ( Ansiktet , Ingmar Bergman, 1958); the recent romantic comedy Cockpit (Mårten Klingberg, 2012); and the trans art film Everything Falls Apart ( Nånting måste gå sönder , Ester Martin Bergsmark, 2016). I will show that the two main shifts in Swedish cinema’s representation of cross-gender performance occurred in the mid-1950s and in the 1990s, due to social changes and changes in the structure of the Swedish film industry. In Swedish cinema, as elsewhere, cross-dressing has never meant any one thing, so we must attend to the specific contexts of its expression in order to understand what it meant.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des industries culturelles; 2-Étude des représentations; 3-Europe (corpus analysé); 5-Créateur.rice LGBTQ+; _Nettoyé

The Queer Film Ecosystem: Symbolic Economy, Festivals, and Queer Cinema's Legs. - Damiens, Antoine (Studies in European Cinema, 2018)
Stresses the crucial importance of LGBT festivals in promoting examples of queer cinema throughout Europe and the USA.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des industries culturelles; 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Review of Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference. - Lindner, Katharina (Transnational Cinemas, 2015)
On the 'Queer Film Culture: Queer Cinema & Queer Film Festivals International Conference', held at the University of Hamburg, 14-15 October 2014, alongside the Hamburg International Queer Film Festival.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Ciné-parcours dans l'Europe contemporaine : routes nécessaires, routes symboliques - Gandolfi, Paola (Cinémas : Revue d'études cinématographiques = Journal of Film Studies, 2010)
Cette vidéaste regarde - et nous fait regarder - la frontière comme un espace mental et matériel : les interviews, la voix over dont le texte apparaît à l'écran, les citations de textes, les images, les sons et le found footage sont combinés de façon à donner un aperçu saisissant et intime à la fois des conditions de vie des femmes (division du travail, prostitution, violence à l'égard des femmes dans les rues, etc.) propres aux régions frontalières, c'est-à-dire se définissant en fonction des contraintes liées à leur position limitrophe, mais offrant une certaine liberté aux gens qui y vivent du fait, justement, de cette position. Il est intéressant de voir comment le road movie permet de réaffirmer la place de l'automobile comme pur moyen de mobilité, mais en même temps comment il nous oblige à nous concentrer sur un autre type de mobilité, que Walter Moser (2008, p. 9) appelle la « médiamotion », soit : une forme de mobilité que nous procurent les médias mais qui, dans un certain sens, remplace ou redouble le déplacement physique en offrant aux êtres humains une expérience presque paradoxale : le contact à distance. On peut également voir dans le road movie contemporain un « road movie interculturel6», parce que la route y trace «un espace imaginaire particulièrement apte à figurer la complexité et les asymétries de l'interculturel » (Gin 2008, p. 41), mais également parce que : l'intetculturalité [...] du road movie résiderait en ce sens dans le mouvement que subit un principe ou une pulsion d'identification culturelle ne pouvant ni se réaliser ou s'assouvir - narrativement, visuellement - dans l'univocité d'un arrêt sur image, ni pour autant s'épuiser on the road Xp. 44). En fait, la mobilité transnationale se situant au centre de cette production filmique «accentuée» donne lieu à un ensemble de tentatives en constante évolution, où les identités culturelles en devenir peuvent être «constamment reformulées dans une perspective future, bien que conditionnées par des liens historiques et des devoirs avec le passé» (Grillo, Riccio et Salih 2000, p. 16), aussi bien que par les liens qu'entretiennent les migrants et les exilés avec leur identité et leur culture d'origine.
Keywords: 1-Cinéma; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé

Contemporary Greek Film Cultures from 1990 to the Present - Kazakopoulou, Tania; Fotiou, Mikela (New Studies in European Cinema, 2017)
This collection of new writing on contemporary Greek cinema builds and expands on existing work in the field, providing a coherent analysis of films which, despite their international importance, have so far received limited critical attention. The volume maps key trends in Greek cinema since the 1990s within the wider context of production and consumption at both national and international levels. It offers a wide range of critical analyses of documentary and avant-garde filmmaking, art house and popular cinema, and the work of established and new directors as well as deliberations on teaching methodologies and marketing strategies. The book seeks to highlight the continuities, mutual influences and common contexts that inform, shape and inspire filmmaking in Greece today.
Keywords: 1-Cinéma; 2-Muséologie critique; 2-Étude des industries culturelles; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); _Nettoyé

Contemporary Jewish Reality in Germany and Its Reflection in Film - Dorchain, Claudia Simone; Wonnenberg, Felice Naomi (De Gruyter, 2012)
The notion of “self” and “other” and its representation in artwork and literature is an important theme in current cultural sciences as well as in our everyday life in contemporary Western societies. Moreover, the concept of “self” and “other” and its imaginary dichotomy is gaining more and more political impact in a world of resurfacing ideology-ridden conflicts. The essays deal with Jewish reality in contemporary Germany and its reflection in movies from the special point of view of cultural sciences, political sciences, and religious studies. This anthology presents challengingly new insights into topics rarely covered, such as youth culture or humor, and finally discusses the images of Jewish life as realities still to be constructed.
Keywords: 1-Cinéma; 2-Histoire/Historiographie critique; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Europe (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

All About Almodóvar’s Men - Rey, Juan; Uceda Pérez, Francisco (Masculinity Studies: Literary and Cultural Representations, 2017)
Pedro Almodóvar is an internationally acclaimed Spanish director. The national and international fascination over Almodóvar's cinema lies in his ability to reflect the problems of contemporary society, his lucidity in combining the urban and the rural, his ability to express the frustrations of modern man, as well as his freshness and spontaneity. Although the vast majority of studies on this Spanish director have focused on women and the gay world, his films are crowded with many types and archetypes of heterosexual men. This groundbreaking edited volume studies the men in the cinema of Almodóvar from a broad yet comprehensive and complementary perspective. Each chapter of All About Almodóvar's Men methodically dissects these male characters—their misery and their greatness, their frustrations and their desires—offering a kaleidoscopic view of man that goes beyond the narrow framework in which many studies have locked the rich cinema of Almodóvar.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Étude des représentations; 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Identités diasporiques; _Nettoyé

Queer/Palestinian Cinema: A Critical Conversation on Palestinian Queer and Women's Filmmaking - Jankovic, Colleen; Nadia, Awad (Camera Obscura: Feminism, Culture, and Media Studies, 2012)
While expanding critiques of pinkwashing have drawn increasing attention to how queer issues in Israel and the Occupied Palestinian Territories are perniciously mobilized by a network of lobby groups, Brand Israel initiatives, and international gay and lesbian organizations, these critiques often fail to consider how queer Palestinians mobilize and understand themselves. This article reports on an October 2011 panel and film screening at Yale University and the Hagop Kevorkian Center for Near Eastern Studies at New York University. “Queer/Palestinian: Critical Strategies in Palestinian Queer and Women's Filmmaking” uniquely focused on questions of queerness and Palestine through a program of eight new Palestinian visual productions. The program brought together Palestinian film scholars, filmmakers, visual artists, and curators for a discussion of queer and feminist artistic practice in relation to Palestinian strategies for resistance. Together, the “Queer/Palestinian” films suggest the urgency for Palestinian visual artists to persistently generate new means of expressing, embodying, and critiquing visions for Palestinian society. Films such as Victoria Moufawad-Paul's Nus Enssas/ صيصنصن (Canada, 2011) and Raafat Hattab's Hourieh (Palestine, 2011) explore issues ranging from queer diasporic solidarity politics and challenges to out/closeted binaries and to the creative reinscription of nakba narratives. Nadia Awad's Two Adaptations of the Same Novel (US, 2011), Suzy Salamy's 1982/2006 (US, 2006), and Moufawad-Paul's Rejoice, O My Heart / يبلق اي حرفا (Canada, 2011) suggest an irreverent queer strategy by undermining the narrative conventions and visual codes of mainstream news media and popular US and Egyptian cinema. Salamy's video, previously projected through mobile exhibition on city buildings, and Eli Rezik's online “web-movies” Living Alone without Me (Palestine, 2011) and Between Us Two (Palestine, 2011) compelled a panel discussion of alternative means of distribution and exhibition. Finally, Alaa AbuAsad's Masturbate bil beit (Palestine, 2011) rounded out the program with an explicitly erotic and unapologetically political version of the meeting of “queer” and “Palestinian.”
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Europe (corpus analysé); 5-Identités diasporiques; _Nettoyé